Forms of Chechen Resistance to Soviet Totalitarian Regime During Deportation (1944 – 1957) - S. Isakieva, Zulay; S. Tsutsulaeva, Sapiyat; I. Khasbulatova, Zulay (International Journal of Psychosocial Rehabilitation, 2020)
One of the important topics in contemporary historical studies is the problem of forced displacement. Many scientifically important aspects of repressed people’s deportation to Kazakhstan are in need of concrete historical study and of historical and theoretical understanding. In this article, based on archival sources, various forms of Chechen and Ingush resistance to the totalitarian regime are analyzed. The reported facts show the special settlements forced nature of the system and the existence of significant administrative barriers to socialization of special settlers from the North Caucasus. The author details the nature of the relationship of local authorities and deported peoples and identifies areas of ideological work of local authorities, especially the formation of protest moods of the peoples and their forms of manifestation. Deported peoples were harassed in moral and social ways, were limited in moving, and many families were separated. It was not guaranteed the right of property and the safety of the personal property of the special settlers, although this right was stipulated in the official documents. However, special immigrants from the North Caucasus, as well as other deported peoples, while in inhumane living conditions in places of settlement, not broken and constantly nurtured the idea of returning to their homeland, resisted the current regime.